Avaliação de modelo de negócio de uma propriedade rural de médio porte de produção de bovinos e ovinos Fazenda Guabeju em Rio Pardo /RS - Medeiros, Marcelo de Mello (Universidade do Vale do Rio dos Sinos, 2015)
The State of Rio Grande do Sul is considered one of the cradles of Brazilian agriculture. In the 1970s, the traditional big rancher just giving way to modern medium-sized properties with higher profitability. Even with this development there are many opportunities in the area for incorporation of modern methods of management and control. This business-oriented article aims to evaluation a model for producing farm of cattle in the south Brazil as well as to purpose new alternatives in order to raise profits. The used methodology was the exploratory case study, with primary and secondary data-collecting. The primary data had been produced by the author. The secondary ones had been produced by the others and become public. Now, there are available to the managers of this farm management tools and analysis as cash flow, income statement, balance sheet, inventory control spreadsheets and indicator spreadsheet. The results show that there are important decisions to be decided by the owners of Farm‟s Guabeju.
Keywords: Plano de negócios; Agropecuária; Gado bovino; Soja; Business plan; Agriculture; Beef cattle; Soybean